Physical Literacy - A Journey of Individual Enrichment: An Ecological Dynamics Rationale for Enhancing Performance and Physical Activity in All - Rudd, James R.; Pesce, Caterina; Strafford, Ben William; Davids, Keith (Frontiers in Psychology, 2020)
Internationally, governments, health and exercise practitioners are struggling with the threat posed by physical inactivity leading to worsening outcomes in health and life expectancy and the associated high economic costs. To meet this challenge it is important to enhance the quality, and quantity, of participation in sports and physical activity throughout the life course to sustain healthy and active lifestyles. This paper supports the need to develop a physically literate population, who meaningfully engage in play and physical activity through the development of functional movement skills in enriched environments. This is a shift away from reductionist approaches to physical activity engagement and maintenance to an ecological dynamics approach that focuses on enrichment to support functional movement skill learning and development. This is an embedded approach to physical literacy that allows learners the space and time to ‘explore–discover’ (ecological psychology) within environments that will lead to a concomitant self-organization of highly intricate network of co-dependent sub-systems (anatomical, respiratory, circulatory, nervous, and perceptual-cognitive) resulting in functional movement solutions for the performance task and enduring positive adaptations to subsystems supporting the physical literacy journey across the life course. ‘Explore-discover adapt’ is at the heart of two contemporary learner-centred pedagogies: Nonlinear Pedagogy and the Athletic Skills Model. Both emphasise the importance of enrichment experiences from an early age, and throughout life course, and both appreciate the inherent complexity involved in the learning process and the importance of designing a rich and varied range of athletic, participatory experiences that will support the embedded development of physical literacy leading to ongoing physical activity for all. The final part of this paper will demonstrate the potential of an ecological dynamics approach for supporting the concept of physical literacy by providing a roadmap for a reliable and valid measurement of physical literacy when considered from both an ecological dynamics perspective and the phenomenology understanding of physical literacy.